Caribbean Report 09-05-1995 - Ransome, Debbie (anchor); Roberts, Michael (interviewee); Ninvalle, Pete (correspondent); Fraser, Tony (correspondent); Rowe, Yvette (correspondent); Hall, Wes (interviewee); Richardson, Richie (interviewee); Roberts, Andy (interviewee); Walsh, Courtney (interviewee) (The British Broadcasting Corporation, 1995)
In this report: Ivor Bird, the younger brother of Antigua's Prime Minister, returned to court on drug-related charges. Police have held one suspect in the shooting of a British tourist in Antigua. In Saint Lucia, the six most powerful trade unions prepare for a two-day strike while banana farmers move into day three of their protest. The Opposition Saint Lucia Labour Party has called on government not to undertake any further capital projects following the allegations of the misuse of UN funds. Caribbean Report states that several regional legal experts have been approached by the St. Lucia's Attorney General to sit on a proposed commission of inquiry to look into the UN funds allegations. Tony Fraser reports on the policy initiatives taken during the tenure of Mr. Ralph Maraj, the sacked Foreign Affairs Minister of Trinidad and Tobago. In cricket, the West Indies squad met with the British press corps as they prepared for their four-month tour of England. Yvette Rowe spoke to members of the West Indies squad. England's Team Manager Ray Illingworth announced the appointment of two specialist coaches, John Edrich and Peter Lever, who were contracted to prepare the English team for the six test series.
1. Headlines with Debbie Ransome (00:00-00:33)
2. Ivor Bird returned to court on drug-related charges in Antigua (00:34-01:04)
3. Police have held one suspect in the shooting of a British tourist in Antigua (01:05-03:43)
4. St. Lucia's trade unions prepare for a two-day strike while banana farmers move into day three of their protest (03:44-06:54)
Keywords: Drug traffic -- Antigua; Indictments -- Antigua; Criminal justice, Administration of -- Antigua; Tourists -- Crimes against -- Antigua and Barbuda; Violent crimes -- Antigua and Barbuda; Strikes and lockouts -- Civil service -- Saint Lucia; Labor disputes -- Saint Lucia; Industrial relations -- Saint Lucia; Banana growers -- Saint Lucia; Saint Lucia -- Politics and government; Political corruption -- Saint Lucia; Capital investments -- Saint Lucia; Governmental investigations -- Saint Lucia; Foreign ministers -- Trinidad and Tobago; Trinidad and Tobago -- Politics and government; Cricket -- Tournaments -- England; Cricket -- West Indies; Cricket -- Press coverage -- Great Britain; Cricket coaches -- England